2017
DOI: 10.1002/nbm.3758
|View full text |Cite
|
Sign up to set email alerts
|

MRI reveals increased tumorigenesis following high fat feeding in a mouse model of triple‐negative breast cancer

Abstract: High animal fat consumption is associated with an increase in triple-negative breast cancer (TNBC) risk. Based on previous MRI studies demonstrating the feasibility of detecting very early non-palpable mammary cancers in simian virus 40 large T antigen (SV40TAg) mice, we examined the effect of dietary fat fed from weaning to young adulthood in this model of TNBC. Virgin female C3(1)SV40TAg mice (n = 16) were weaned at 3–4 weeks of age and then fed either a low fat diet (LFD) (n = 8, 3.7 kcal/g; 17.2% kcal from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
5
8
0
Order By: Relevance
“…As previously reported (Mustafi et al, 2017), DIO increased the total tumor burden in C3(1)-TAg mice (Fig. 1D), and this increased burden was due, in part, to the presence of more tumors in obese mice ( Fig.…”
Section: Diet-induced Obesity Promotes Tnbc Stemness and Tumor Formatsupporting
confidence: 87%
“…As previously reported (Mustafi et al, 2017), DIO increased the total tumor burden in C3(1)-TAg mice (Fig. 1D), and this increased burden was due, in part, to the presence of more tumors in obese mice ( Fig.…”
Section: Diet-induced Obesity Promotes Tnbc Stemness and Tumor Formatsupporting
confidence: 87%
“…Past MRI studies from this laboratory have demonstrated both an increase in the recruitment of arteries to cancerous mammary glands in SV40Tag transgenic mice with TNBC 22 and an increase in invasive mammary cancers due to a high fat diet in this mouse model. 12 Using serial MRI, this study confirms the increase and observes its pattern over 5 weeks, beginning the scans at an earlier time point to observe any changes in the mammary glands throughout the development of the cancer. Additionally, this study shows the corresponding increase in mammary gland volume, as well as blood volume in the mammary glands, using TOF MRI.…”
Section: Discussionsupporting
confidence: 73%
“…The mammary glands of HAFD-fed mice exhibited irregular and enlarged ducts, dilated blood vessels, and more mature white adipose tissue, while the mammary glands of LFD-fed mice exhibited fewer/smaller blood vessels, and more abundant brown adipose tissue. 12,25 The connection between high fat diet/obesity and breast cancer has been attributed in part to adipose tissue dysfunction. 26 The increase in blood volume and vascular density in the mammary glands of mice fed an HAFD as determined by MRI in this study has been corroborated with histological images using H&E staining.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations